Developing kurikulum merdeka textbooks to teaching critical thinking skills for elementary school students - Sucahyo, Eko; Ningtyas, Rani Kusuma; Fithriyah, Nurhidaya (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2025)
Students tend to use fewer thinking activities in learning. Consequently, learning is often dominated by conventional learning models. In addition, learning only uses available textbooks and causes students to be less involved in learning. Students mostly take the role of listeners, take notes on what the teacher says, and work on the questions given according to the examples. This study aimed to develop textbooks based on the Kurikulum Merdeka that can improve the critical thinking skills of elementary school students. The method used in this study is the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques used are observation, testing, and documentation. This study uses teaching module validation instruments, question validation, and textbook feasibility tests. The results of the study show that the use of this textbook can have a positive impact on students' critical thinking skills significantly, as well as provide positive feedback from teachers and students on the learning process as evidenced by the t count value of 8.513> t table 1.724. It is hoped that this research can contribute to learning in elementary schools and be a reference for the development of other teaching materials in the Kurikulum Merdeka.